Syntheses, structures, physical and electronic properties of quaternary semiconductors: Cs[RE9Cd4Se18] (RE = Tb–Tm). Issue 13 (3rd March 2016) - Lin, Hua; Chen, Hong; Liu, Peng-Fei; Yu, Ju-Song; Zheng, Yu-Jun; Ali, Khan Muhammad; Chen, Ling; Wu, Li-Ming
Abstract : Five new quaternary rare-earth selenides, Cs[RE9 Cd4 Se18 ] (RE = Tb–Tm) with closed cavities are reported. Abstract : Five new quaternary rare-earth selenides, Cs[RE9 Cd4 Se18 ] (RE = Tb–Tm), which are the first examples with closed cavities in the quaternary A/RE/Cd/Q (A = alkali metal; RE = rare earth metal; Q = chalcogenide) system, have been synthesized by high-temperature solid state reactions with a modified reactive CsCl flux. Single crystal X-ray diffraction analyses show that these isostructural materials adopted a known BaV13 O18 -structure type in the trigonal space group R 3̄ (no. 148) with cell parameters of a = 17.773(2)–17.489(6) Å, c = 9.918(2)–9.765(5) Å and Z = 3. The structure is composed of MSe6 (centered by disordered RE and Cd) and RESe6 octahedra that share edges to form a 3D framework, inside which the cuboctahedral Se12 closed cavities accommodate Cs cations. It is interesting to note that these compounds exhibit atomic distributions different from the recently reported Mn-compounds Cs[RE9 Mn4 Se18 ]. In Cd-compounds, Cd and RE atoms are statistically mixed only at one of the 18f sites; the rest of the RE atoms are fully occupied at the two framework sites: 18f and 3a. Moreover, the theoretical studies have greatly aided the understanding of the site-preference about a Cd atom in the 3D framework. The synthesis, structural characterization, electronic band structure as well as physical properties of the title compounds are also discussed.